Prevalence and Determinants of Oral Potentially Malignant Disorders among Malayali Tribal Tobacco Users in Yelagiri Hills, Tamil Nadu, India: A Community-Based Cross-Sectional Study - Delfin Lovelina Francis; Anitha Logaranjani K; Pratap Kumar Jena (National Journal of Community Medicine, 2026)
Introduction: Oral potentially malignant disorders (OPMDs) are important precursors of oral cancer and are strongly associated with tobacco use. Evidence on OPMDs among tribal populations in India remains limited. This study estimated the prevalence and clinical distribution of OPMDs among Malayali tribal tobacco users in Yelagiri Hills, Tamil Nadu, and examined associated tobacco-use characteristics. Methods: A community-based cross-sectional study was conducted among 240 current tobacco users aged ≥18 years. Data on sociodemographic characteristics and tobacco-use behaviours were collected using a structured questionnaire. Clinical oral examinations were performed according to WHO criteria for OPMD diagnosis. Factors associated with OPMD were assessed using multivariable logistic regression. Results: The mean age was 45.7 ± 18.9 years and 92.9% were male. Smoking-only tobacco use was reported by 57.9%, smokeless-tobacco use by 38.8%, and dual use by 3.3%. Overall OPMD prevalence was 60.0% (95% CI: 53.7-66.0), with oral leukoplakia being the most common lesion (37.1%). Tobacco-use duration exceeding 10 years was independently associated with OPMD presence (aOR: 8.98; 95% CI: 3.75-21.48; p